Pitch anything : an innovative method for presenting, persuading and winning the deal - Klaff, Oren (McGraw-Hill Education LLC, 2011)
When it comes to delivering a pitch, Oren Klaff has unparalleled credentials. Over the past 13 years, he has used his one-of-a-kind method to raise more than.